Single-stage Open Lobectomy and Modified Ravitch Procedure in an Infant with Coexisting Severe Pectus Excavatum and Congenital Cystic Adenomatous Malformation - Solomon Ifeanyi Ukwuani; Isah Abdullahi; Muideen Adegbola Ajadi; Abubakar Umar (Wolters Kluwer Medknow Publications, 2024)
Coexisting congenital cystic adenomatous malformation of the lungs and severe pectus excavatum (PE) is an uncommon presentation that poses significant management challenges. Conventionally managed in a staged manner, there are increasing reports of superior outcomes with single-staged concurrent repair with minimally invasive techniques (video-assisted thoracoscopic surgery [VATS] and minimally invasive repair of PE [MIRPE]). The outcome of a single-stage open repair for both anomalies has not been previously reported to the best of our search. We report the successful single-stage management of a 9-month-old infant with both anomalies who had an open lobectomy and modified Ravitch procedure. We aim to report the feasibility and safety of a single-stage concurrent repair of both conditions using open techniques, as VATS and MIRPE are not readily available in our environment.